2017
DOI: 10.3389/fmars.2017.00222
|View full text |Cite
|
Sign up to set email alerts
|

Marine Animal Microbiomes: Toward Understanding Host–Microbiome Interactions in a Changing Ocean

Abstract: All animals on Earth form associations with microorganisms, including protists, bacteria, archaea, fungi, and viruses. In the ocean, animal-microbial relationships were historically explored in single host-symbiont systems. However, new explorations into the diversity of microorganisms associating with diverse marine animal hosts is moving the field into studies that address interactions between the animal host and a more multi-member microbiome. The potential for microbiomes to influence the health, physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
130
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(134 citation statements)
references
References 100 publications
(108 reference statements)
4
130
0
Order By: Relevance
“…These processes of co-evolution have been documented by several studies carried out in the organization and composition of host microorganisms (microbiome) in different species [1][2][3][4]. The microbiome is currently considered a functional organ which is fundamental for the host organism, given that studies have shown that this organ is highly dynamic and adaptable, likewise plays an important role in physiological adaptation processes, metabolism, and development [1,2,[4][5][6]. The study of the role of the microbiome for years was limited to those organisms that could be susceptible to culture, the use of techniques based on molecular information (AFLP and RFLP) and denaturing gradient gel electrophoresis (DGGE) could reveal the presence of some species not cultured, but the gel resolution was being the main limitation since a single band could contain more than one sequence [7].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…These processes of co-evolution have been documented by several studies carried out in the organization and composition of host microorganisms (microbiome) in different species [1][2][3][4]. The microbiome is currently considered a functional organ which is fundamental for the host organism, given that studies have shown that this organ is highly dynamic and adaptable, likewise plays an important role in physiological adaptation processes, metabolism, and development [1,2,[4][5][6]. The study of the role of the microbiome for years was limited to those organisms that could be susceptible to culture, the use of techniques based on molecular information (AFLP and RFLP) and denaturing gradient gel electrophoresis (DGGE) could reveal the presence of some species not cultured, but the gel resolution was being the main limitation since a single band could contain more than one sequence [7].…”
Section: Introductionmentioning
confidence: 93%
“…Higher multicellular organisms have coexisted and co-evolved with resident microorganisms in a relatively harmonious relationship over millions of years, forming a complex organism called holobiont. These processes of co-evolution have been documented by several studies carried out in the organization and composition of host microorganisms (microbiome) in different species [1][2][3][4]. The microbiome is currently considered a functional organ which is fundamental for the host organism, given that studies have shown that this organ is highly dynamic and adaptable, likewise plays an important role in physiological adaptation processes, metabolism, and development [1,2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the help of recent advances in next generation sequencing, microbiome-associated biomarkers, just like ccfDNA, can be used in clinical practice for risk prediction, diagnosis and progression of a disease, or to predict and modulate response to treatment [13,14]. In marine ecology, microbial biomarkers are also being used for measuring the impact of anthropogenic activities on marine ecosystems [15,16]. In the present work, we have combined the concept of liquid biopsy and the use of FTA cards to develop a liquid biopsy-based sampling method that involves fixation of nucleic acids on FTA cards.…”
Section: Introductionmentioning
confidence: 99%
“…Surfaces of marine animals were found to be a unique habitat for colonization by microorganisms, and the microbial communities associated with living surfaces showed a pronounced variety [1]. Till recently, studies focused on the colonization of benthic organisms such as sponges [2–6], bryozoans [7], and cnidarians, within which are included mainly corals [813].…”
Section: Introductionmentioning
confidence: 99%